Research ethics for social scientists between ethical conduct and regulatory compliance - Israel, Mark.; Hay, Iain. (London : SAGE, 2006)
Ethics is becoming an increasingly prominent issue for all researchers across the western world. This comprehensive and accessible guide introduces students to the field and encourages knowledge of research ethics in practice.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social sciences -- Research -- Moral and ethical aspects